Hubungan Antara Persepsi Tentang Program Multimedia Dan Minat Belajar Dengan Motivasi Belajar Siswa Jurusan Multimedia - Mufarochah, Siti (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2016)
Abstract. This study aims to prove a correlation between perceptions of multimedia program and learning interest of student’s learning motivation on multimedia department. The samples of this study are 80 students of SMK YPM 3 Taman Sidoarjo. The results of this study are there is a correlation between perceptions of multimedia program and learning interest of studen’t learning motivation. According to the data analysis result by using Multiple Regression Analysis known F=7.792 with a significance level (p)